Faktor-Faktor yang Mempengaruhi Minat Masyarakat Mengaplikasikan Produk Perbankan Syariah di Jawa Timur - Andrian Dwi Rahmad Firdaus; Devano Hayunda Fachrizal; Angelo Zauqi Rafl Priambodo; Abiyyah Muhammad; Intan Nurhasanah; Ach. Yasin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The growth of the Islamic banking business in Indonesia has exhibited a substantial rise in accordance with the expanding public understanding of Islamic financial concepts. However, public enthusiasm in adopting Islamic banking products remains variable, notably in East Java Province, which is characterized by strong religion and local culture. The purpose of this research is to examine how the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) factors, local culture, religion, Islamic financial literacy, government support, perceived risk, and social environment affect the public's interest in utilizing Islamic banking products. This research also employs the Theory of Planned Behaviour (TPB) as a theoretical framework to explain the link between attitudes, subjective norms, perceived behavioral control, and usage intention. This study uses a survey technique and a quantitative methodology. Data were acquired via questionnaires delivered to persons in East Java Province who are acquainted with Islamic banking services. The sample approach employed was purposive sampling. Data analysis was undertaken using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the support of SmartPLS software. The findings show that public interest in using Islamic banking products is positively and significantly impacted by religion, Islamic financial literacy, the social environment, and a number of UTAUT2 characteristics. Meanwhile, perceived danger has a detrimental influence on use intention. These results underscore the significance of strengthening Islamic financial literacy and adopting instructional initiatives that include social, cultural, and technical variables to stimulate public interest in Islamic banking. This research is designed to give both theoretical and practical contributions to the development of marketing strategies and policy formation for Islamic banking in Indonesia.